Uji Sitotoksik Ekstrak Etanol Daun Keladi Tikus (Typhonium Flagelliforme L), Kemangi (Ocimum Sanctum L) Dan Pepaya (Carica Papaya L) Terhadap Sel Hela - Putri, Dhinar Asti Pradana; , Maryati, Ph.D., Apt (2016)
Cervix cancer is the most cancer that suffered by woman in the world include in Indonesia. Some existing anticancer treatment have not satisfying, so this experiment is to explore the Indonesian plan to find new anticancer agents. This experiment aimed to determine the cytotoxic effects of extract ethanol leaf rodent tuber (Typhonium flagelliforme L), basil (Ocimum sanctum L), and papaya (Carica papaya L) to HeLa cells. Extraction was conducted by maceration method using ethanol extract 96%. Cytotoxic test performed by using MMT assay method to obtain IC50 values. The content of the compunds in the extract were identified using Thin Layer Chromatography (TLC) with various spray reagent. This experiment conclude IC50 of extract ethanol leaf rodent tuber, basil and papaya were 404,5 µg/mL, 373,8 µg/mL, and more than 500 µg/mL respectively. Extract ethanol of rodent tuber, basil and papaya has no cytotoxic effect. Thin layer chromatography result that extract ethanol of rodent tuber leaf, basil and papaya contain alkaloids, phenolic, flavonoids, saponins and terpenoids.